Działania niemieckich wojsk pancernych na froncie wschodnim w lecie 1941 r. - Kuczmarski, Marek (Acta Universitatis Lodziensis. Folia Historica, 2001)
During the World War II, particularly in its first years, the German armoured troops played important and specific role. Such formations were basic instrument of hostilities and decided about the course of the whole war, although at first there were only few people, who believed armoured forces would be effective. The German armoured divisions, that appear to be precursors of contemporary motorized formations, deserve special attention. The literature about the history of the German-Soviet war in the years of 1941-1945 described the participation of such formations only on the backgroud of general process of hostilities. But it is possible to notice the historical significance of the German armoured troops’ activities in that war, knowing the newly published documents and books. There is the lack of synthetic studys that would touch the entirely of German armoured troops’ activities, although the literature about the German-Soviet war, both in Poland and abroad, is very rich. That is why I decided to choose that particularly interesting theme. The most important sources used in my paper were memoires, remebrances and studies about tanks and armoured troops in wider sense. The main task of my article is the description of problems connected with Hitler’s military and political preparations for the attack of the Soviet Union, the extension and concentration of motorized troops on German-Sowiet frontier and their participation in each section of Eastern front in summer 1941. The entire study was divided into three parts, what is compatible with three strategical ofensive directions of Army Groups: „North”, „Centre”, „South”. The paper also describes attempts of taking Leningrad, the battle of Somolensk and the great battle of Kiev in September 1941. The beginning of defence of the Army Group „Centre” on the direction Moscow and the considerable reducing of offensive intensity on the other directions (the siege of Leningrad and the end of Kiev battle in the middle of September 1941) are the final ceasure of the article.